Do patients need advice and information to prevent infections – results of a single centre structured survey. Issue 4 (December 2022) - Voigt, M.; Schaumann, R.; Barre, F.; Mayr, E.; Lehmann, W.; Hawellek, T.; Kaba, H.E.J.; Wüstefeld, S.; Scheithauer, S.
Summary: Background: Healthcare-associated infections are a major burden for hospitals, leading to morbidity and mortality and unnecessary medical costs. They can probably be reduced through what is known as patient empowerment. This study aims to address the question of whether patients are interested in receiving infection prevention and control information. Methods: Patients were asked in structured interviews whether they would like more information on infection prevention and control. Inclusion criteria comprised 2 groups of patients. Group 1 were patients undergoing elective total endoprosthesis (TEP) and Group 2 were patients tested positive for meticillin-resistant Staphylococcus aureus (MRSA). Results: The response rate was 38.4 % (163/425 patients). Approximately 75 % of the patients were interested in information on infection prevention and control. The topics of interest differed between the two patient groups: MRSA patients had a higher need for infection prevention and control information. TEP patients showed a high acceptance of antiseptic body wash and a willingness to pay for it themselves. Information given to patients should be group-specific and timely. Conclusion: Our data suggest a lack of information on infection prevention and control among patients and underline the importance of patient empowerment. The willingness of patients to pay personally for antiseptic wash should be assessed further.